1966
DOI: 10.1149/1.2424086
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics and Mechanism of Oxidation of Superpurity Aluminum in Dry Oxygen

Abstract: A vacuum microbalance and furnace assembly was constructed and employed to determine the growth kinetics of oxide films on aluminum. Using electropolished foil samples of geometric area 80 cm2, and making corrections for spurious weight changes arising from thermal diffusion effects, film thickness changes as small as 0.3Aå could be reliably detected. In addition to kinetic data, the structure of representative oxide films was examined by electron microscopy. It was found that only “amorphous” oxide grew for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 11 publications
2
53
0
Order By: Relevance
“…Several researchers have studied the thermal oxidation of aluminum and found that an air-formed oxide film develops when aluminum is heated in air or oxygen to a temperature above 723 K. An amorphous oxide film is formed initially and then -alumina crystals develop at the metal-oxide interface. [1][2][3][4] As the oxidation temperature increases, the crystallinealumina is gradually transformed from the amorphous aluminum oxide by the inward diffusion of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied the thermal oxidation of aluminum and found that an air-formed oxide film develops when aluminum is heated in air or oxygen to a temperature above 723 K. An amorphous oxide film is formed initially and then -alumina crystals develop at the metal-oxide interface. [1][2][3][4] As the oxidation temperature increases, the crystallinealumina is gradually transformed from the amorphous aluminum oxide by the inward diffusion of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide film formed is initially amorphous and -alumina crystals develop at the metaloxide interface. [2][3][4][5] Shih et al conducted thermogravimetric analysis (TGA) and X-ray powder diffractometer analysis on pure aluminum samples that had been heated in an air atmosphere from room temperature to 883 K. They found an apparent weight gain at 832 K due to the transformation of gibbsite to diaspore. They found the thermally formed oxide films to be comprised of complex oxides: gibbsite, diaspore, -Al 2 O 3 , and -Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the oxidation of pure aluminium, the literature is primarily focussed on oxidation in the solid state (see, e.g. [24,31,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]). …”
Section: Microstructural Observations Of Oxide Filmsmentioning
confidence: 99%
“…In solid-state oxidation of aluminium, it is generally observed that the initial oxide to form is amorphous [49][50][51][52][53][54][55]. When held at an elevated temperature, a crystalline oxide is observed [31,51,[54][55][56][57], often identified to be γ-alumina [31,51,54,55,[58][59][60][61].…”
Section: Microstructural Observations Of Oxide Filmsmentioning
confidence: 99%
See 1 more Smart Citation